New research shows that supplementing with beta- Hydroxy beta-methylbutyrate improved oxygen consumption and increased endurance for cyclists. - Burke, E. R.
A study out of Wichita State University in Wichita, Kan., by Michael Vukovich, Ph.D., investigated the effect of HMB on maximal oxygen consumption (VO2 max) in endurance-trained cyclists--with the goal being increased VO2 max and endurance time to the point where athletes reached exhaustion. Eight cyclists randomly completed three supplementation periods. Each period was two weeks in duration, followed by a two-week washout period. Supplements were 3 g/day HMB, 3 g/day leucine (LEU) and 3 g/day placebo (control). Prior to and following each supplementation period, subjects completed a VO2 max test. Two weeks of HMB supplementation resulted in a significant increase in VO2 max (pre-test was 4.57 L/minute; post was 4.75 minute--a 4 percent increase). VO2 max was unaffected by supplementation with leucine (pre 4.70 L/minute; post 4.61 L/minute--a 1.9 percent decrease) or the control (pre 4.71 L/minute; post 4.60 L/minute--a 2.5 percent decrease). In addition, HMB supplementation resulted in a significantly greater time to reach VO2 max, whereas leucine and the control did not affect this time (HMB: pre 21.9 minutes, post 22.7 minutes; LEU: pre 22.2 minutes, post 21.6 minutes; control: pre 22.4 minutes, post 21.6 minutes). The researchers concluded that HMB supplementation may have positive effects on performance by increasing VO2 max and endurance time to exhaustion. Up to this point, research showed increases only in the performance of strength-trained athletes.